Efecto del ácido ascórbico en dieta, sobre la repuesta Nutricional y metabólica en juveniles de tilapia roja (Oreochromis mossambicus x Oreochromis niloticus) - Olaya Vera, Kevin Leonel (2022)
Red tilapia is of great economic importance for aquaculturists in the livestock areas of our country. The objective of this research was to evaluate the effect of ascorbic acid supplementation in a pelleted diet on the nutritional and metabolic response in juvenile red tilapia (Oreochromis mossambicus x Oreochromis niloticus).